The effect of shape, blanching methods and flour on characteristics of restructured sweetpotato stick. - S. Utomo, Joko; Che Man, Yaakob; Abdul Rahman, Russly; Saad, Mohd Said (Wiley-Blackwell, 2008)
The blanching methods and controlling dry matter content used in the preparation of mashed sweetpotato (SP) for producing restructured sweetpotato stick (RSS) were studied. The two shapes of trimmed tuber were sliced and diced. Blanching was conducted by (i) boiling for 2 min in water at 100 °C and (ii) blanching in water at 100 °C containing 1% (w/v) sodium tripolyphosphate (STP) for 2 min. Controlling the dry matter content of dough was conducted by adding SP flour (0%, 5%, 10%, 15% and 20%). Chemical and physical characteristics were determined on the final product. The results from this study showed that blanching in 1% STP for 2 min improves colour and ash content of fried stick. Mixing of 5% SP flour with mashed SP produces suitable dough for further processing. RSS can be produced by a combination of blanching in 1% STP and mixing with 5% SP flour produce an intermediate hardness, high lightness and low redness colouration of RSS.